Analysis of phenolic profile, total phenolic content and antioxidant activity in Anacardium occidentale leaves - Sassi, Assia; Haron, Normah; Khattak, Muhammad Muzaffar Ali Khan; Mat Jusoh, Hanapi (Rynnye Lyan Resources, 2022)
Anacardium occidentale young leaves are consumed traditionally as part of a Southeast Asian diet. The regular consumption is believed to have beneficial effects on health in general and potentially against type 2 Diabetes mellitus due to its high content of polyphenols. This study was aimed to investigate the polyphenol content of the plant using two methanol extracts; Free Phenolic Extract (FPE) and Bound Phenolic Extract (BPE) as well as highlight the presence of six phenolic acids and flavonoids namely; gallic acid, sinapinic acid, caffeic acid, ferulic acid, quercetin and kaempferol using High performance liquid chromatography-photodiode array (HPLC-UV-Vis). The results for polyphenols and flavonoids content showed high amounts of total polyphenols in BPE with 8.5±0.57 mg GAE/g as well as high amounts of total flavonoids in both extracts FPE and BPE with 0.58±0.06 and 0.86±0.05 mg QE/g respectively (p<0.05). The presence of these polyphenols was further confirmed by measuring the antioxidant activity through the scavenging of the free radical DPPH which showed an IC50 value for FPE (5.17±0.64 µg/ mL, BPE (4.96±0.12 µg/mL) compared to the positive control ascorbic acid (4.91±0.43 µg/mL). The high-performance liquid chromatography-photodiode array confirmed the presence of all four targeted phenolic acids with the highest amount showing in gallic acid and sinapinic acid in BPE with 148.12±6.44 µg gallic acid/g dry weight and 47.02±1.94 µg sinapinic acid/g dry weight respectively. As for flavonoids, quercetin was present in both extracts with 20.38±1.22 µg/g dry weight in BPE and 5.21±0.1 µg/g dry weight in FPE while Kaempferol was not detectable in either extract. These findings confirmed the importance of A. occidentale as a rich source of polyphenols which can be further investigated to determine its effects in-vitro and in-vivo on non-communicable diseases such as type 2 diabetes.